2006
DOI: 10.1086/498276
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Designs and the Evolution of Functional Diversity

Abstract: According to conventional wisdom, functional diversity is exclusively a consequence of species having evolved adaptations to fill different niches within a heterogeneous environment. This view anticipates only one optimal combination of trait values in a given environment, but it is also conceivable that alternative designs of equal fitness in the same environment might evolve. To investigate that possibility, we use a genetic algorithm to search for optimal combinations of 34 functional traits in a realistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
214
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(229 citation statements)
references
References 72 publications
10
214
1
1
Order By: Relevance
“…Future work aimed at directly linking functional traits to mechanisms of species coexistence, therefore, will benefit by incorporating data on fine-scale environmental heterogeneity [18] and temporal variation in resource availability and demographic performance. Contrary to the CWM-optimality hypothesis, more species than expected also had significantly positive relationships between ROR and DCWM, reflecting the success of alternative functional strategies and the high-dimensional nature of species coexistence [17,25,41,42]. For instance, several species with low WD that are particularly abundant in dry forests of our study system (e.g.…”
Section: Discussioncontrasting
confidence: 78%
“…Future work aimed at directly linking functional traits to mechanisms of species coexistence, therefore, will benefit by incorporating data on fine-scale environmental heterogeneity [18] and temporal variation in resource availability and demographic performance. Contrary to the CWM-optimality hypothesis, more species than expected also had significantly positive relationships between ROR and DCWM, reflecting the success of alternative functional strategies and the high-dimensional nature of species coexistence [17,25,41,42]. For instance, several species with low WD that are particularly abundant in dry forests of our study system (e.g.…”
Section: Discussioncontrasting
confidence: 78%
“…Any single trait in this leaf economic spectrum responds to multiple environmental factors in ways constrained by functional linkages to other foliar and non-foliar traits reflecting a variety of plant functions at the whole plant level Lechowicz 2006b, Reich 2014). This creates multiple possibilities for combinations of traits that yield approximately equal performance at the whole plant level (Marks and Lechowicz 2006a). Although the LES is strong across broad scales, it is typically much weaker on small gradients and within communities (e.g., Funk and Cornwell 2013), so that along the main LES trade-off axes, traits retain a significant ability to vary independently of each other, i.e., show scatter perpendicular to an LES trade-off axis.…”
Section: Discussionmentioning
confidence: 99%
“…For diverse systems, such as tropical forest tree communities, many empirical studies have shown that functional traits of species are often distributed in ways that are consistent with mechanisms of community assembly, such as habitat filtering (6, 7), but lack depth to evaluate underlying mechanisms. More biophysical studies on mechanisms are often confined to small samples of species (8) or to theoretical simulations (9) and therefore fail to explain the community-level consequences of physiological differences among species. We lack studies that provide detailed trait-based biophysical models to understand the possible consequences of functional trait differences across species for niche separation, which in turn may act as one of the mechanisms contributing to species coexistence in species-rich communities (3,10), such as tropical forests (11).…”
mentioning
confidence: 99%
“…Second, to maintain their high photosynthetic rates at high resource levels, acquisitive tree species require high stomatal conductance and, in turn, a high hydraulic conductivity of the watertransporting wood to sustain a high transpiration rate (9,32). Highly conductive wood, however, involves a higher risk of hydraulic failure, i.e., the cavitation of xylem water columns, under dry conditions (30,33).…”
mentioning
confidence: 99%